The Process of Development and Types of Pedagogical Diagnostics - Andrey Ostapenko (International Society of Philosophy and Cosmology, 2014)
The author analyzes earlier published article "developmental psychology", by V. I. Slobodchikov's, specifying the offered terminology and discussing a correlation of processes of maturing, personality, character formation and transformation. Proposed model is a combination of these processes making development. In terms of this model and the definition of diagnostics offered by V. I. Slobodchikov the author's typology of pedagogical diagnostics aspects